The unacceptability of the digraph to the turkic writing (based on the Arabic script of the old Turkish, Kazakh and Uzbek writing) - Kydyrbayev, K.; Kozhabekova, Sh.B. (Journal of Oriental Studies, 2021)
After the approved alphabet was heavily criticized by the public, the President of Kazakhstan K. Tokayev instructed the Ministry of culture and sports to improve the new alphabet, and the projects of several authors were discussed. Among the developers of the project were those who wanted to use various methods and techniques to place the sounds of the Kazakh language on the 26 buttons of the keyboard. Some of them want to transmit sounds, which is characteristic for the Kazakh language, shared and borrowed sounds through the digraphs, and trigraphs, and someone who promoted the law "dayekshe" A. Baitursynov, referring to the law of synharmonism as the basis. By giving examples of the projects presented in this article, we will prove that the use of digraphs in the Kazakh script is unacceptable.